MAIN UNITS OF VERBAL COMMUNICATION - Egamberdiyeva Iroda; Qodirov Xalilullo; Tirkasheva Shahnoza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Verbal communication plays a very important role in our lives. We use verbal communication to express our thoughts and feelings and in daily communication.Verbal communication has its advantages and disadvantages. It is also divided into types. We use one of these types depending on our processes.